Analysis of periodical use at the U.P. Medical Library a study of the use patterns of the periodical literature in medicine - Dizon, Julio Jr. E.; Rosal, Rosvida R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1982)
An evaluation of the extent of use of the periodical collection of the UP Medical Library was conducted during the first semester of academic year 1981-1982. The objectives of the study are: 1) to identify the journal titles that are most heavily used, and 2) to determine the years in the life of the journals which provide much of the information sought by the users. Three concomitant hypotheses were formulated in studying the patterns of use of medical periodical literature. These are: 1) a few periodical titles account for a greater part of the total use of the periodical collection; 2) periodicals published within the last five years provide a large part of the information sought by the users; and, 3) periodical usage gradually declines with increasing age of the journals. The study was based on the analysis of cancelled periodical request/charge slips collected from July 7, 1981 through October 26, 1981.
Findings show that 75 per cent of the periodical titles selected to represent the total journal holdings were used at least once during the study period. The journals used were ranked in order of decreasing frequency of use. It was observed that a few titles in the collection account for the high usage of the periodicals. The first fifty heavily-used titles, representing 16 per cent of the total journals used, account for almost 66 per cent of the total use of the periodical collection. The last five years of journal life account for 70 per cent of total journal usage. This finding clearly demonstrates that current publications are sought by the users and journal usage varies inversely with the increasing age of journals.
Data and findings of this study are useful, as bases for planning, decision-making and improvement of the periodical collection of the UP Medical Library. Results of this study are likewise recommended as guides for other libraries of similar nature which are in the process of developing or building up their journal collection.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Medical libraries--Philippines.; Medicine--Periodicals--Use studies; University of the Philippines Manila. College of Medicine. Library